Prenatal Diagnosis of a Fetus with Ring Chromosomal 15 by Two- and Three-Dimensional Ultrasonography - Ingrid Schwach Werneck Britto; Sandra Regina Silva Herbest; Giselle Darahem Tedesco; Carolina Leite Drummond; Luiz Claudio Silva Bussamra; Edward Araujo Júnior; Rodrigo Ruano; Simone Hernandez Ruano; José Mendes Aldrighi (Hindawi Limited, 2014)
We report on a prenatal diagnosis of ring chromosome 15 in a fetus with left congenital diaphragmatic hernia (CDH) and severe intrauterine growth restriction (IUGR). A 31-year-old woman, gravida 2 para 1, was referred because of increased nuchal translucency at gestational age of 13 weeks. Comprehensive fetal ultrasound examination was performed at 19 weeks revealing an early onset IUGR, left CDH with liver herniation, and hypoplastic nasal bone. Three-dimensional ultrasound (rendering mode) showed low set ears and depressed nasal bridge. Amniocentesis was performed with a result of a 46,XX,r(15) fetus after a cytogenetic study. A 1,430 g infant (less than third percentile) was born at 36 weeks. The infant presented with respiratory failure and died at 2 h of life. Postnatal karyotype from the umbilical cord confirmed the diagnosis of 15-ring chromosome. We described the main prenatal 2D- and 3D-ultrasound findings associated with ring chromosome 15. The interest in reporting the present case is that CDH can be associated with the diagnosis of 15-ring chromosome because the critical location of the normal diaphragm development is at chromosome 15q26.1-q26.2.